2012
DOI: 10.3892/ol.2012.985
|View full text |Cite
|
Sign up to set email alerts
|

Pomolic acid induces apoptosis in SK-OV-3 human ovarian adenocarcinoma cells through the mitochondrial-mediated intrinsic and death receptor-induced extrinsic pathways

Abstract: Abstract. The cytotoxic effect of pomolic acid (PA), a pentacyclic triterpene isolated from flowers of Osmanthus fragrans var. aurantiacus Makino, was investigated in SK-OV-3 human ovarian adenocarcinoma cells. PA dose-dependently inhibited the viability of SK-OV-3 cells. PA-induced apoptosis was further characterized by detection of cell surface annexin V and sub-G1 apoptotic cell populations. The number of cells immunostained with annexin V-fluorescein isothiocyanate (FITC) increased following treatment with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 21 publications
2
9
0
Order By: Relevance
“…The effect of pomolic acid on reactive oxygen species (ROS) generation, cell migration and cell cycle arrest were also studied. It has been reported that pomolic acid exhibits anticancer and apoptotic effects in SK-OV-3 human ovarian adenocarcinoma cells through mitochondrial-mediated intrinsic and death receptor-induced extrinsic pathways (17). To the best of the authors' knowledge, the current study of antitumor effects of pomolic acid in SK-MEL-2 human malignant melanoma cells is the first such attempt, and has not been reported in earlier published work on this natural product.…”
Section: Introductionmentioning
confidence: 93%
“…The effect of pomolic acid on reactive oxygen species (ROS) generation, cell migration and cell cycle arrest were also studied. It has been reported that pomolic acid exhibits anticancer and apoptotic effects in SK-OV-3 human ovarian adenocarcinoma cells through mitochondrial-mediated intrinsic and death receptor-induced extrinsic pathways (17). To the best of the authors' knowledge, the current study of antitumor effects of pomolic acid in SK-MEL-2 human malignant melanoma cells is the first such attempt, and has not been reported in earlier published work on this natural product.…”
Section: Introductionmentioning
confidence: 93%
“…Compound 3 ( Figure 5) was identified from its spectral data and by comparison with reports corresponding to compounds in the literature as the rare ursane-type pentacyclic triterpenoid, pomolic acid. Pomolic acid (3) is the 19-hydroxy derivative of the more common ursolic acid and has previously been isolated from other plant families including Rosaceae (Ju et al, 2003), Sapotaceae (Lee et al, 2005a), Oleaceae (Saimaru et al, 2007;Yoo et al, 2013), Staphyleaceae (Cheng et al, 2010), and the blueberry fruit (Neto, 2011). Natural and semisynthetic ursane-type triterpenoids are believed to have the potential as candidates for the design of multi-target bioactive compounds, with focus on their anticancer effects (Salvador et al, 2012) and pomolic acid is reported to induce apoptosis in some cancer cell lines (Vasconcelos et al, 2007;Yoo et al, 2013;Youn et al, 2012).…”
Section: Characterization Of Compoundsmentioning
confidence: 99%
“…Triterpenoids so far isolated from the Dichapetalaceae are the dammarane-type -dichapetalins (Achenbach et al, 1995;Addae-Mensah et al, 1996;Fang et al, 2006;Long et al, 2013;Osei-Safo et al, 2008); friedelane-type -friedooleananes, zeylanol, canophyllal, and canophyllol (Addae-Mensah et al, 2007;Darbah, 1994;Fang et al, 2006) and the lupane-type -betulinic acid and betulonic acid (Addae-Mensah et al, 2007;Fang et al, 2006). Pomolic acid isolation has reportedly occurred usually with the oleanane-type and the lupane-type triterpenoids (Saimaru et al, 2007;Neto, 2011;Yoo et al, 2013).…”
Section: Characterization Of Compoundsmentioning
confidence: 99%
“…Increasing evidence has indicated that these two apoptotic pathways are not isolated; crosstalk occurs between them. In the intrinsic pathway, mitochondria are the critical mediators of apoptosis (27)(28)(29). Certainstimuli, such as anticancer drugs, can induce permeabilization of the outer mitochondrial membrane and activate the mitochondrial pathway.…”
Section: Discussionmentioning
confidence: 99%